Top 5 Priorities That Will Shape the Future Of Retail Banking Industry In India - BHADRAPPA HARALAYYA (Journal of Advanced Research in HR and Organizational Management, 2021)
Retail banking refers to the delivery of financial services by a bank to individual customers rather than to corporate clients, companies, or other banks. The main retail banking products include savings and transaction accounts, mortgages, personal loans, debit cards, and credit cards. India experienced a surge in retail banking after introducing financial sector reforms in 1992. The retail banking industry in India has fast emerged as one of the major contributors to the overall growth of the banking sector in the recent past. In the current business environment, the Indian banking industry is putting strategic emphasis on retail banking products to ensure profitability and lasting customer relationships. This is clear in rising trends in retail loans and deposit shares on commercial bank balance sheets and a persistent increase in the number of bank branches. How to cite this article: Haralayya B. Top 5 Priorities That will Shape The Future of Retail Banking Industry in India. J Adv Res HR Organ Mqmt 2021; 8(1&2): 17-18.